La investigación social en Diseño como una práctica cultural. (2021)
The project activity as investigation in design, includes the creative stage, model creation and the production of objects. The methods help to be rigorous, disciplined and creative; and the creativity does not reduce rigor to the process, but the investigation in design is the experience by itself of the design, it is not the design and the investigation divided; it is integral: to segment it, to standardize or to try to define it does not make sense but although it is complex to describe how investigation is done in design, The best thing is to do is to understand the concept as a social fact in the daily activity of the designer, who wonders and solves problems to do it, investigates; the really important thing is the attitude of the investigator in design, the world vision and the ethics, for such investigation leads towards the obtaining of beneficial results for the humanity.